Spatial Distribution of Drifted-wood Hazard following the July 2017 Sediment-hazards in the Akatani river, Fukuoka Prefecture, Japan - Christopher Gomez; Mariko Shimizu; Sayaka Kanai; Norifumi Hotta; Candide Lissak (Forum Geografi, 2020)
In recent years, heavy rainfall leading to floods, landslides and debris-flow hazards have had increasing impacts on communities in Japan, because of climate change and structural immobilism in a changing and ageing society. Decreasing rural population lowers the human vulnerability in mountains, but hazards can still leave the mountain to the plains and sea, potentially carrying drifted-wood. The aim of the paper is to measure the distribution of wood-debris deposits created by the 2017 Asakura disaster and to rethink the distribution and spatial extension of associated disaster-risk zoning. For this purpose, the authors: (1) digitized and measured the distribution of drifted-wood, (2) statistically analyzed its distribution and (3) calculated the potential impact force of individual drifted timber as a minimal value. The results have shown that there is a shortening of the wood debris as they travel downstream and that the geomorphology has an important control over deposition zones. The result of momentum calculation for different stems’ length show spatially differentiated hazard-zones, which limit different disaster-risk potentials. From the present finding, we can state that we (1) need to develop separate strategies for sediments and wood debris (2) and for wood hazards, zonations can be generated depending on the location and the size of the deposited trees that differs spatially in a watershed.